Performance Measurement Using Value For Money Concept in Village Government - Reski, Nur Awalia (STIEM BONGAYA, 2021)
This study aimed to determine the measurement of performance in the Village Government of Jabal Nur, Kec. Kodeoha, North Kolaka Regency in 2015-2019 using the concept of Value For Money. Performance measurement is one of the factors for a private or public organization. Performance measurement is used as a control tool in an organization to evaluate the results of activity and determine the success of the management carried out by an organization. The application of the value for money concept is important for the government as a public service because the implementation of this concept will provide benefits for assessing: 1) the effectiveness of public services, 2) the quality of public services, 3) spending allocations that are more oriented to the public interest, and 4) increasing public cost awareness as the root of the implementation of public accountability. The results of this study indicate that the performance of the Jabal Nur village government has been said to be economical because the percentage ratio has never exceeded 100%; in terms of efficiency, government performance is efficient even though the first 3 years are in balanced efficiency, but in years 4 and 5 the level of efficiency has increased, and from in terms of the effectiveness of the performance of the village government of Jabal Nur has been effective even though in 2017 the level of effectiveness was according to. Still, the following year the level of effectiveness increased again.